Los cuadernos de Pío | Una vocación que nace del río ﻿(traducción al inglés) - Fiedczuk, Adriana Silvina (Museo Pío Collivadino, 2023)
Archives are necessary in society because they promote knowledge, safeguarding and preserving our memories. Each archive contains a unique character that portrays both cultural and administrative activities, showing a clear reflection of the evolution of societies. Archives safeguard decisions, performances and memories. They enable us to contextualise the object of study, therefore, allowing us to do a much more complete analysis. The collection “Los cuadernos de Pío” (Pío’s Journals) aims to present the reader with documents of Pío Collivadino’s personal archive in instalments which tackle several themes related to the artist’s life and his paintings. The artist made the decision of showing this collection in a systematic and selective manner, with the intention of recording many events that took place in both his public and private life. The quantity and variety of documents and material that has been retrieved and organised is immensely valuable: ranging from photographs, letters, drafts, diplomas, posters, catalogues, amongst others. `Revising this archive allows an insight to both the artist’s professional evolution and his personal life, desires, thoughts, feelings, and passions, by exploring the unique relation he established with his context and contemporary folk. All these aspects influenced his life and career choices, with their lights and shadows, together with his public figure, loved by many, but also controversial to others. Becoming acquainted with this versatile artist’s life, from his beginnings to his public recognition, is of general interest. In “A Vocation Born from the River”, we share documents from the Pio Collivadino Museum Archive that reflect his first artistic incursions and his eagerness to explore diverse artistic disciplines. Our aim is to portray the beginnings of Pio Collivadino, the famous Buenos Aires` painter.
Pio’s journals | A vocation born from the river
Textos e idea: Adriana Fiedczuk; Diseño gráfico: Estefanía D. Nigoul. Traducción: Docentes en formación - Espacio: Prácticas Discursivas de la Comunicación Escrita IV. Docente: Prof. Yamila N. Tornello. Profesorado de Inglés - ISFD y T 18 - 2024 - Banfield. Bareiro, Yamila Macarena. Cardenes, Melina del Rosario. Mussin, Adriana Paula Lorena. Nuñez, Romina Giselle. Perez Fernandez, Araceli Edith. Perez, Guadalupe. Pérez, Marisol. Piluso Mulhall, Lola Esther. San Martín, Iván Alejandro.
Keywords: Biografías; Arte Argentino; Historia del Arte; Cultura; Arte